2005
DOI: 10.1159/000086496
|View full text |Cite
|
Sign up to set email alerts
|

Intractable Diarrhoea due to Congenital Enterocyte Defects

Abstract: Background: Intractable diarrhoea of infancy represents a severe problem with a high degree of morbidity and mortality. These cases demand dedicated care from both parents and medical staff as there are no easy remedies. The rarity of patients indicates that progress in understanding these disorders requires concerted international efforts to pool resources and patients. Regular reviews of publications in the field are required to disseminate advances and to air hypotheses and diagnostic criteria. Methods: Thi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2014
2014
2014
2014

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 112 publications
0
1
0
Order By: Relevance
“…In 1995 Guarino et al indicated that regardless of etiology and age, patients with severe diarrhea who usually need PN should be grouped under ''severe and protracted diarrhea'' (3). After 2000, authors focused on enteropathies because of primary enterocyte abnormalities and immune-mediated disorders (IMD), but some of them decided to investigate anomalous presentations of common etiologies first (10,11). The age at onset of diarrhea of patients varied in studies of children up to 1 or 2 years old (3,4,9).…”
Section: Discussionmentioning
confidence: 99%
“…In 1995 Guarino et al indicated that regardless of etiology and age, patients with severe diarrhea who usually need PN should be grouped under ''severe and protracted diarrhea'' (3). After 2000, authors focused on enteropathies because of primary enterocyte abnormalities and immune-mediated disorders (IMD), but some of them decided to investigate anomalous presentations of common etiologies first (10,11). The age at onset of diarrhea of patients varied in studies of children up to 1 or 2 years old (3,4,9).…”
Section: Discussionmentioning
confidence: 99%